Usability perception of the health information systems in Brazil: the view of hospital health professionals on the electronic health record. (7th April 2022) - Welchen, Vandoir; Matte, Juliana; Giacomello, Cintia Paese; Dalle Molle, Franciele; Camargo, Maria Emilia
Abstract : Purpose: The purpose of this paper is to validate and measure the overall evaluation of electronic health record (EHR) and identify the factors that influence the health information systems (HIS) assessment in Brazil. Design/methodology/approach: From February to May 2020, this study surveyed 262 doctors and nurses who work in hospitals and use the EHR in their workplace. This study validated the National Usability-focused HIS Scale (NuHISS) to measure usability in the Brazilian context. Findings: The results showed adequate validity and reliability, validating the NuHISS in the Brazilian context. The survey showed that 38.9% of users rated the system as high quality. Technical quality, ease of use and benefits explained 43.5% of the user's overall system evaluation. Research limitations/implications: This study validated the items that measure usability of health-care systems and identified that not all usability items impact the overall evaluation of the EHR. Practical implications: NuHISS can be a valuable tool to measure HIS usability for doctors and nurses and monitor health systems' long-term usability among health professionals. The results suggest dissatisfaction with the usability of HIS systems, specifically the EHR in hospital units. For this reason, those responsible for health systems must observe usability. This tool enables usability monitoring to highlight information system deficiencies for public managers. Furthermore, the government can create and develop actions to improve the existing tools to support health professionals. Social implications: From the scale validation, public managers could monitor and develop actions to foster the system's usability, especially the system's technical qualities – the factor that impacted the overall system evaluation. Originality/value: To the best of the authors' knowledge, this study is the first to validate the usability scale of EHR systems in Brazil. The results showed dissatisfaction with HIS and identified the factors that most influence the system evaluation.